Oman and the Arab–Israeli Conflict: The Reflection of a Pragmatic Foreign Policy - Rabi, Uzi (Israel Affairs, 2005)
The foreign policy of the Sultanate of Oman has differed markedly from those of other Arab Gulf countries, let alone other Arab states. Many a time, governments and political leaders throughout the region have been bewildered by Muscat’s nonconformist stance. Perhaps nowhere was the independence of Oman’s foreign policy more evident than in its attitude toward Israel and the Arab-Israeli conﬂict. The focus of this article is Oman’s policy toward the Arab-Israeli conﬂict from 1970 to the present day. In arguing that it is just another component of the country’s multifaceted foreign policy, the discussion traces Oman’s political history and offers insights into how this foreign policy has been shaped. It identiﬁes the logic behind Oman’s policy initiatives, and assesses its ability to adapt to changing regional and international environments.
Keywords: Vie politique -- Oman -- 1970-2020